Influence of Sickle Cell Gene on the Allelic Diversity at the msp-1 locus of Plasmodium falciparum in Adult Patients with Severe Malaria - Patel, Dilip Kumar (Mediterr J Hematol Infect Dis, 2015)
Although several studies have supported that sickle cell trait (HbAS) protects against falciparum malaria, the exact mechanism by which sickle gene confers protection is unclear. Further, there is no information on the influence of the sickle gene on the parasitic diversity of P. falciparum population in severe symptomatic malaria. This study was undertaken to assess the effect of the sickle gene on the parasite densities and diversities in hospitalized adult patients with severe falciparum malaria. The study was carried out in 166 adults hospitalized subjects with severe falciparum malaria at Sickle Cell Clinic and Molecular Biology Laboratory, Veer Surendra Sai Institute of Medical Sciences and Research, Burla, Odisha, India. They were divided into three groups on the basis of hemoglobin variants HbAA (n=104), HbAS (n=30) and HbSS (n=32). The msp-1 loci were genotyped using a PCR-based methodology. The parasite densities were significantly high in HbAA compared to HbAS and HbSS. The multiplicity of infection (MOI) and multi-clonality for msp-1 were significantly low in HbSS and HbAS compared to HbAA. The prevalence of K1 (p<0 .0001) and MAD20 (p=0.0003) alleles were significantly high in HbAA. The RO33 allele was detected at a higher frequency in HbSS and HbAS, compared to K1 and MAD20. Sickle gene was found to reduce both the parasite densities and diversity of P. falciparum in adults with severe malaria.